Relationship Between Integrated Marketing Communication and Brand Equity - Theodora, Nadia - (International Journal of Social Science and Business, 2021)
This study will try to explain the relationship between the application of integrated marketing communication (IMC) and its influence to the establishment and development of brand equity and also will look at the role of each element of integrated marketing communication to brand equity. This article uses the literature review method by summarizing the result of various credible studies that highlight the relationship between IMC and brand equity. The result shows that there is a direct relationship between the simultaneous application of all elements of IMC to the formation of brand equity. But partially each element of IMC has its own impact on the formation of brand equity, depending on the context of the company, region, time, andÂ target consumers.Keywords : Integrated Marketing Communication, Brand, Brand Equity, IMC